2007
DOI: 10.1590/s0034-72992007000400008
|View full text |Cite
|
Sign up to set email alerts
|

Estudo da relação entre a respiração oral e o tipo facial

Abstract: Breat hing is responsible for facial and cranial morphology development. Aim: investigate in order to see if there is any relationship between oral breathing and facial type. Material and Methods: 119 male and female teenagers, with ages ranging between 15 and 18 years. The sample was separated in two groups: A-50 teenage oral breathers, 28 males and 22 females; and group B-69 teenage nasal breathers, 37 males and 32 females. The sample was collected at the Centro de Atendimento e Apoio ao Adolescente do Depar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
1
36

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(57 citation statements)
references
References 4 publications
3
17
1
36
Order By: Relevance
“…Corroborating the present study, a recent research 14 with oronasal and nasal breathing found that the orofacial measurements were similar between the two groups. The findings of that study were similar to those obtained in different studies 7,30 , which, even when using different methodology, suggest that respiratory mode cannot be considered as a primary factor for orofacial changes. However, the respiratory mode diagnosis only through Speech-Language Pathology evaluation is considered a limitation of the current study.…”
Section: Discussionsupporting
confidence: 88%
“…Corroborating the present study, a recent research 14 with oronasal and nasal breathing found that the orofacial measurements were similar between the two groups. The findings of that study were similar to those obtained in different studies 7,30 , which, even when using different methodology, suggest that respiratory mode cannot be considered as a primary factor for orofacial changes. However, the respiratory mode diagnosis only through Speech-Language Pathology evaluation is considered a limitation of the current study.…”
Section: Discussionsupporting
confidence: 88%
“…Despite conflicts between studies in the literature that showed that there is not a direct relationship between the measurement by caliper and perceptual evaluation, it is important to note that different methods of objective assessment were used [15][16][17] , which changes the perspective of facial analysis that cannot be employed in the perceptual evaluation. Nevertheless, the relationship between the caliper measurements used in this study proved to be very accurate with the perception of face typology, as are numerical relations that are implicitly used to evaluate the perception of face typology, hypothesis confirmed according to the presented results.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the relationship between height and width allows inferences about the functional changes, the relationship between the hemi-faces also allows this characterization, especially being related to masticatory changes, parafunctional habits and disorders of the temporomandibular joint 17 . This evaluation also revealed a substantial relationship between analyzes performed, observing nearly a full compatibility between tests to determine symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…Clinical speech-language pathology evaluation of the respiratory mode was conducted by a speech-language therapist with expertise in the area, who was responsible for the screening and speech-language assessments of the hospital sector, according to Bianchini et al 2 . Mode of breathing was considered adequate (Nasal Breathing Group -NB group) when the patients' lips were occluded at rest and exclusive nose respiration was used with a possibility of labial sealing ≥3 minutes, measured by a digital chronometer, TIMEX manufactured (T5K491SR/TI Manaus, AM, Brasil).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, oral breathing presents multifactorial etiology, either due to obstruction of the upper airways or habits that cause air to pass through the mouth 2 . Such a respiratory mode may alter the growth of maxillary bones with a decrease in their transverse dimension 3 , reduce the tone of the orofacial muscles (especially the lower lip Rev Odontol UNESP.…”
Section: Introductionmentioning
confidence: 99%